The Impact of Community Radio in Promoting Girl-Child Education: A Case of Eye Radio Juba Central Equatoria South Sudan - Kiko Evaline Martin Kenyi (Uganda Christian University, 2024)
The purpose of the study was to investigate the impact of community radio in promoting girl-child education: a case of Eye Radio Juba central Equatoria South Sudan. The study was guided by the following objectives; examining the status of community radio in the promotion of girl-child education in Juba South Sudan, assessing the role of community radio in promoting girls’ education in Juba South Sudan and examine the strategies used in community radio to promote girl-child education in Juba South Sudan. The study employed the use of a case research design where qualitative research approach was used. The method of data collection used during the study was interviews. A sample of 10 key informants who were selected staff of Eye Radio in Juba, Central Equatoria, South Sudan i.e. the head of programs, presenters, the station manager, producers and journalists was gotten using purposive sampling method. The study findings highlighted Eye Radio’s pivotal role in promoting girls' education in Juba, South Sudan through effective community radio strategies. The station's commitment to raising awareness, fostering community engagement, and advocating for girls' educational rights is evident in their diverse and impactful programming. By addressing local challenges, leveraging strategic partnerships, and embracing multimedia platforms, Eye Radio not only educates and empowers its audience but also influences public perception and mobilizes support for girls' educational opportunities. Despite operational challenges, their sustained efforts highlight Eye Radio as a trusted advocate and catalyst for positive change in promoting educational equity and gender equality in the region. Last, the study recommended continuous capacity building for Eye Radio staff, sustainable funding mechanisms beyond traditional donors, enhanced community engagement strategies involving local stakeholders, leveraging digital platforms to expand reach, and developing robust monitoring and evaluation frameworks to assess and improve program impact on promoting girl-child education.
Undergraduate research